Molecular epidemiology of aquatic environments: challenges from sampling to implementation of surveillance programs - Mendoza-Guido, Bradd; Montiel-Mora, Jose R.; Ureña-Salazar, Cristina; Barrantes, Kenia; Chacón, Luz (Frontiers in Public Health, 2025)
Pathogens are introduced into wastewater through human and animal fecal discharge, ultimately contaminating aquatic environments such as rivers and beaches. Molecular tools are commonly used to track outbreak-related pathogens in wastewater due to numerous advantages such as enhanced sensitivity, speed, and specificity. However, many low- and middle-income countries (LMICs) face challenges in developing adequate sanitation infrastructure and accessing or implementing high-cost technologies, which hampers the integration of environmental surveillance into national and regional public health programs. This mini-review summarizes key challenges in applying molecular techniques for water-based epidemiological monitoring of waterborne pathogens in resource-limited settings. We examine obstacles related to sampling aquatic environments, including collecting samples from rivers and concentrating analytes from complex matrices such as wastewater and polluted river or beach waters, emphasizing the importance of preserving environmental representativeness. We provide a brief overview of the most widely used PCR-based technologies for detecting waterborne pathogens and antimicrobial resistance genes (ARGs), discussing their advantages and limitations. We also examine advanced high-throughput technologies, often inaccessible in LMICs, and emerging portable tools that may enhance detection where laboratory infrastructure is limited. Finally, through applied examples, we show how environmental data can make pathogen surveillance more accessible while bridging laboratory research with public health practice.